Pemanfaatan Limbah Minyak Jelantah menjadi Lilin Aromaterapi sebagai Inovasi Ramah Lingkungan di Desa Buddagan - Nur Alifia Faryanti; Devita Antikasari; Amalina Hanuna; Putri Indah Ayuni (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
Converting used cooking oil into aromatherapy candles represents an environmentally sustainable solution for household waste management while supporting community-based economic development. This research examines the process and results of a participatory empowerment initiative conducted in Buddagan Village, aimed at producing value-added aromatherapy candles from used cooking oil. Employing a qualitative descriptive methodology with a participatory approach, the study involved 60 housewives as active contributors. Program activities were implemented through direct, in-person sessions encompassing education on health and environmental hazards of improper oil disposal, hands-on candle-making training, and basic instruction on product marketing. The production process consisted of oil purification using activated charcoal, mixing with stearic acid, heating, adding colorants and fragrances, and molding. Data were collected through direct observation of participant involvement, skill development, and product quality, and analyzed inductively. The results demonstrate increased environmental awareness, enhanced technical competence, and the successful production of aromatherapy candles with satisfactory shape, fragrance, and burning consistency.